Navigating farmer interests in climate policy processes and negotiations - Chevallier, Romy; Tuyishime, Norbert (2024)
This policy briefing was prepared for the Eastern Africa Farmers Federation (EAFF). It emphasizes the importance of active farmer engagement in shaping climate policies that support sustainable agriculture and enhance resilience to climate change. It outlines the key areas where farmer engagement is essential, focusing on the current negotiating streams within the United Nations Framework Convention on Climate Change (UNFCCC). It analyses the developments at the 28th Conference of Parties in Dubai (COP28) in December 2023 and at the 60th sessions of the Subsidiary Body for Scientific and Technological Advice and the Subsidiary Body for Implementation (SB60) in Bonn in June 2024. It also looks ahead to COP29 and recommends key areas for EAFF engagement and attention.